Peningkatan Pemahaman Mahasiswa Blok Keperawatan Jiwa Melalui Pembelajaran Kooperatif Tipe STAD (Student Teams Achievement Divisions) Pada Materi Terapi Modalitas Keperawatan Jiwa - Tutu April Ariani (STIKes Patria Husada Blitar, 2019)
Upaya yang dilakukan untuk meningkatkan kemampuan berpikir kritis yaitu dengan menerapkan model pembelajaran yang dipandang akomodatif bagi peningkatan kemampuan berpikir kritis mahasiswa maupun aktivitas belajar, yaitu dengan menerapkan model pembelajaran kooperatif. Tipe-tipe pembelajaran kooperatif diantaranya adalah Metode STAD (Student Teams- Achievement Divisions). Penelitian tindakan kelas ini dilaksanakan di Se- mester III Prodi S1 Keperawatan FIKES Universitas Muhammadiyah Malang, Kelas A. Kondisi lain yang terikat bahwa latar belakang mereka cukup beragam,mereka terdiri dari beragam suku, tempat asal, sehingga secara keseluruhan Semester III relatif cukup heterogen. Pengamatan dari ceklist merupakan data utama yang mengamati aspek: bekerjasama, menyampaikan gagasan, bertanya, memperhatikan pertanyaan teman, menanggapi, mampu mngerti secara mendalam tentang materi, berperan aktif dalam kelompok, dapat menjadi penengah, menjelaskan, menarik kesimpulan materi. Penelitian tindakan memiliki 4 tahapan yaitu: planning, doing action, observation dan reflection, yang berjalan melalui 2 siklus/ putaran (setiap putaran dilakukan 2 kali pertemuan). Tahap terakhir dari proses ini adalah: Reflection. Hasil dari observasi diorganisir dan dianalisis. Tahap ini dapat digunakan oleh instruktur untuk memberikan umpan balik berdasar hasil pengamatan. Berikutnya didiskusikan tindakan yang sudah sesuai untuk meningkatkan pemahaman mahasiswa di mata kuliah Keperawatan Kesehatan Jiwa. Many ways can improve to critical thinking skills of student are applying learning models that are considered accommodative for improving stu- dents’ critical thinking skills and learning activities by applying coopera- tive learning models. The types of cooperative learning include the STAD Method (Student Teams-Achievement Divisions). This action research was conducted in one class of third semester in Bachelor Graduate Nursing Program Study FIKES at the University of Muhammadiyah Malang, espe- cially Class A. Other conditions that were bound were that their back- grounds were quite diverse, they consisted of various tribes, places of ori- gin, so that overall Semester III was relatively heterogeneous. Data col- lected by observation sheets, among others, were observed: cooperation in groups, gave ideas, asked questions, pay attention to friend questions, gave responses, ability to understand material, participation in groups, ability to mediate if there are groups who misunderstand, ability to ex- plain and conclude material discussed. The action through 4 stages, are respectively: planning, action, observation, and reflection, carried out in two cycles (each cycle carried out twice meeting). The final stage of this process is Reflection. The results obtained in the observation phase are collected and analyzed. At this stage, the instructor can reflect on the results of observations and discussions to examine whether the actions taken can improve students’ understanding of the Mental Health Nursing course. The results of data analysts carried out in stages will be used as a reference for planning the next cycle. The results showed a decrease in misunderstanding, there were 3 people (11.11%) out of 27 students who did not reach comprehension of competency, because the accumulation of values <80. There was an increase in the passing of the competency test to 19 people (88.89%) with the above scores 80.00. It is expected that this STAD method can be applied to other subjects so that overall competency test graduation increases.